2002
DOI: 10.1094/phyto.2002.92.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia and Nitrous Acid from Nitrogenous Amendments Kill the Microsclerotia of Verticillium dahliae

Abstract: This study examined the mechanisms by which nitrogenous amendments such as meat and bone meal kill the soilborne plant pathogen Verticillium dahliae. The effect of nitrogen products from the amendments on the survival of microsclerotia of V. dahliae was examined by solution bioassay and soil microcosm experiments. Ammonia and nitrous acid but not their ionized counterparts, ammonium and nitrite, were toxic to microsclerotia in bioassays. In microcosms, addition of meat and bone meal (2.5%) to an acidic loamy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(70 citation statements)
references
References 40 publications
1
68
0
1
Order By: Relevance
“…Leoni and Ghini (2006) and Dos Santos and Bettiol (2003) established negative correlations between EC and the incidence of Phytophthora nicotianae in citrus and Sclerotioum rolfsii in bean, respectively. Tenuta and Lazarovits (2002) observed a decrease in the viability of Verticillium microsclerotia as a consequence of the accumulation of nitrogenous compounds. In the present study, sludge application decreased soil pH and increased EC, as well as the concentration of N-NO 3 − .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Leoni and Ghini (2006) and Dos Santos and Bettiol (2003) established negative correlations between EC and the incidence of Phytophthora nicotianae in citrus and Sclerotioum rolfsii in bean, respectively. Tenuta and Lazarovits (2002) observed a decrease in the viability of Verticillium microsclerotia as a consequence of the accumulation of nitrogenous compounds. In the present study, sludge application decreased soil pH and increased EC, as well as the concentration of N-NO 3 − .…”
Section: Discussionmentioning
confidence: 92%
“…Concerning the use of organic amendments, several cases of controlling this pathogen have been reported in the literature. Tenuta and Lazarovits (2002) demonstrated that ammonia and nitrous acid from liquid swine manure and nitrogenous amendments inhibited microsclerotia germination. Goicoechea et al (2004) suggested that organic amendments could stimulate defence mechanisms, providing an ecological and efficient means for the control of pepper wilt caused by V. dahliae.…”
Section: Introductionmentioning
confidence: 99%
“…When the pH drops below 5.5, NO 2 − is converted to HNO 2 (nitrous acid) (pK a occurs at pH 3.3). Nitrous acid is approximately 300-500 times more toxic to microsclerotia than NH 3 (155) and is also toxic to many plant pathogens. most influenced by soil buffering capacity (156) as nitrification lowers soil pH only in poorly buffered soils.…”
Section: Klosterman Et Almentioning
confidence: 99%
“…most influenced by soil buffering capacity (156) as nitrification lowers soil pH only in poorly buffered soils. Both ammonia and nitrous acid were highly effective at reducing the microsclerotia in acidic soils (155). Because of the sitespecific nature of soil pH and organic matter, efficacy of these products in pathogen suppression is inconsistent.…”
Section: Klosterman Et Almentioning
confidence: 99%
“…Adverse effects of organic nutrient sources on seed germination have correlated with the concentration of NH 4 + in amendments, for example, chicken manure (Wong et al, 1983), while sources high in cation exchange capacity such as peat can help ameliorate the toxic effects of NH 4 + relative to inorganic NH 4 + sources, thereby improving root development at moderate rates of application (Abbès et al, 1995). Ammonia was also suggested to be a biotoxic causative factor in controlling verticillium wilt (Verticillium daliae) with organic amendments (Tenuta and Lazarovits, 2002).…”
Section: Core Ideasmentioning
confidence: 99%